HER2 amplification status in breast cancer: a comparison between immunohistochemical staining and fluorescence in situ hybridisation using manual and automated quantitative image analysis scoring techniques. Issue 7 (23rd June 2005) - Ellis, C M; Dyson, M J; Stephenson, T J; Maltby, E L
Abstract : Aims: To compare the results of breast cancer sections with HercepTest™ immunohistochemistry (IHC) scores ranging from 0 to 3+ with fluorescence in situ hybridisation (FISH) for HER2 amplification. The HER2 digital scoring application of the Micrometastasis Detection System (MDS™) was used, together with manual scoring of FISH and HercepTest, to determine whether this system provides an accurate alternative. Methods: Paraffin wax embedded sections were stained using HercepTest and analysed by eye and automated quantitative image analysis. FISH was performed using the PathVysion™ fluorescent probe and scored by eye and automated quantitative image analysis using MDS. Results: Of 114 cases, 26% were amplified by FISH, whereas only 18% scored 3+; 32% of IHC 2+ cases were amplified by FISH, and one showed borderline amplification. Six percent of IHC negative cases (0 or 1+) were amplified by FISH, and one showed borderline amplification. Of IHC 3+ cases, 10% were non-amplified by FISH. Classification discrepancies were seen in 18% of HercepTest cases scored by eye and using the MDS system. MDS was consistent with visual FISH scoring and correctly differentiated most ambiguous visual IHC scores. Conclusions: FISH provides a more accurate and consistent scoring system for determining HER2 amplification than HercepTest. The MDS system provides a reliable, consistent alternative to visual IHC and FISH scoring. IHC is still a valuable technique to aid in identification of isolated or heterogeneous tumour populations for subsequent FISH analysis, and a combined FISH and HercepTest approach to all breast cancer cases may be the most efficient strategy.